The influence of meteor measurement errors on the heliocentric orbits of meteoroids. (1st October 2020) - Hajduková, Mária; Kornoš, Leonard
Abstract: The present study demonstrates that measurement errors may significantly change meteor nominal orbital parameters and may create spurious meteoroid orbits, which can lead to a distortion of the true meteoroid populations. We tested the dependence of the heliocentric orbital elements on the reduced meteor data, the pre-atmospheric velocity and the position of the radiant, using a simple model of the geometry of a meteoroid's encounter with the Earth. A simulated change of 1 deg in the radiant position and 1 ​km ​s −1 in the pre-atmospheric velocity of a geminid-kind of meteoroid gave a dispersion of ± 0.01 au in its perihelion distance and ± 2 deg in its inclination. A simulated positive error of 1 ​km ​s −1 in the pre-atmospheric velocity applied to a typical perseid-type test particle produced orbits of which more than one third were hyperbolic. Highlights: We tested the dependence of the heliocentric orbital elements on the reduced meteor data, the pre-atmospheric velocity and the position of the radiant. A simulated positive error of 1 km/s in the pre-atmospheric velocity applied to a typical perseid-type test particle produced orbits of which more than one third were hyperbolic. Analyses based on individual orbits set high requirements for the accuracy of the data measured. Error dispersions of the data set limits beyond which the interpretations cannot be pushed.